A sociological analysis of the production, marketing and distribution of contemporary popular music by Zambian musicians - Kazadi, Kanyabu Solomon (Rhodes University, Faculty of Humanities, Department of Sociology, 2015)
The purpose of this research was to gather information about the production, marketing and distribution of Zambian contemporary music by Zambian musicians. Very little information has been documented about the development of the Zambian music industry, particularly from the perspective of those within the industry. As a result this study attempted to add to this knowledge. To achieve this Pierre Bourdieu's theoretical concepts of 'fields' and 'habitus' were used to gain an understanding of what affects the creation of art forms such as music as well as the structures and underlying processes within the music industry. The concept of 'fields' usefully framed an explanation of the struggles and connections within the various fields in the industry and a view of the Zambian music industry in relation to the international industry. To gather the data necessary for this research a qualitative approach was utilised involving semistructured in-depth questionnaires from twenty-three interviewees. These interviewees were selected from various sectors of the music industry in an attempt to gain a holistic perspective of the industry in the 21st century. There were four subgroups: the artists (singers, rappers and instrumentalists), managers, radio DJs, and a miscellaneous group made up of the remaining participants, a Sounds Arcade manager, a music journalist, the National Arts Council Chairperson, a Zambia Music Copyright Protection Society (ZAMCOPS) administrator, and the then President of the Zambia Association of Musicians (ZAM). With the limited exposure to formal musical, instrumental and production training, musicians, instrumentalists, managers and studio production personnel interviewed had had to learn their craft on-the-job. This limited knowledge appears to add to the hindrance of the development of careers and the industry, particularly in terms of how to register and distribute music correctly to earn royalties and protect their intellectual property against piracy. From an institutional level piracy is being addressed more forcefully with the introduction of holograms and the tightening of policies and structures to do with the music industry.
Keywords: Popular music -- Zambia; Musicians -- Zambia; Sound recording industry -- Zambia; Popular music -- Production and direction -- Zambia; Popular music -- Marketing; Intellectual property -- Zambia; Copyright -- Royalties -- Zambia